2017
DOI: 10.1002/ana.24904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative muscle ultrasound detects disease progression in Duchenne muscular dystrophy

Abstract: Objective We assessed changes in quantitative muscle ultrasound data in boys with Duchenne muscular dystrophy (DMD) and healthy controls to determine if ultrasound can serve as a biomarker of disease progression. Two approaches were used: grey scale level (GSL), measured from the ultrasound image, and quantitative backscatter analysis (QBA) measured directly from the received echoes. Methods GSL and QBA were obtained from six unilateral arm/leg muscles in 36 boys with DMD and 28 healthy boys (age 2–14 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 16 publications
3
76
0
4
Order By: Relevance
“…One approach simply relies upon measuring muscle thickness because atrophy reduces muscle bulk . The second approach is to quantify the echointensity of the muscle, which is expected to increase in most disorders as an increasing proportion of fat and connective tissue leads to increased reflectivity . Quantification of echointensity can be most easily performed by means of a gray scale level (GSL) analysis, in which an image is converted to a standard photo format, with the relative whiteness/darkness of the image obtained using a commercially available program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One approach simply relies upon measuring muscle thickness because atrophy reduces muscle bulk . The second approach is to quantify the echointensity of the muscle, which is expected to increase in most disorders as an increasing proportion of fat and connective tissue leads to increased reflectivity . Quantification of echointensity can be most easily performed by means of a gray scale level (GSL) analysis, in which an image is converted to a standard photo format, with the relative whiteness/darkness of the image obtained using a commercially available program.…”
mentioning
confidence: 99%
“…Quantification of echointensity can be most easily performed by means of a gray scale level (GSL) analysis, in which an image is converted to a standard photo format, with the relative whiteness/darkness of the image obtained using a commercially available program. An alternative approach is to assess the direct backscatter of the acoustic signal; while this approach is likely to provide “truer” data, because it is not postprocessed by means of various proprietary algorithms, most commercial ultrasound systems do not provide such raw values . Regardless of the approach to quantification, performing such measurements of echointensity is not simple.…”
mentioning
confidence: 99%
“…It is still unclear which EIM variables are best suited to measure changes, and the choice for a specific variable depends on the disease being studied. Consequently, multiple studies have used different outcomes including, among others, single and multifrequency measures, single muscle and composite measures, single phase values, and phase ratios . Prior studies have shown that reactance is least susceptible to variability in subcutaneous fat content or electrode configuration .…”
Section: Discussionmentioning
confidence: 99%
“…For analyses, 4 different frequencies, 50, 100, 211, and 300 kH Z , were chosen on the basis of prior EIM studies in neuromuscular diseases. In addition, phase ratios were calculated for 50/211 kH Z and 100/300 kH Z …”
Section: Methodsmentioning
confidence: 99%
“…Over the years, it has evolved into a distinct ultrasound subspecialty. A vast amount of literature provides evidence regarding the value of neuromuscular ultrasound in the diagnostic evaluation of neuromuscular disorders (more key references are provided in Data S1 online) . As a result, neuromuscular ultrasound has become a fundamental diagnostic tool in many electrodiagnostic labs, clinics, and radiology centers.…”
Section: Introductionmentioning
confidence: 99%